PALEOMAGNETISM OF THE VOLYN AND MOGILEV-PODOLIA VENDIAN SERIES OF THE SOUTH-WESTERN PART OF THE EAST-EUROPEAN PLATFORM - Glevasskaya A.M.; Mikhailova N.P.; Kravchenko S.N. (My University, 2001)
On the basis of T- and AF-demagnetisation carried out in the course of studies of Neo-Proterozoic paleobasalts (of the Volyn Series, Lower Vendian) and terrigenous rocks (of the Grushki Suite, Lower Vendian and of the Mogilev-Podolia Series, Upper Vendian) from outcrops of the Volyn and Podolia Peridniester regions (the SW part of the EEP), three main NRM components were identified. This was confirmed by magnetic-mineralogical data. Component A was characterised by inverse polarity. Its VGPs, localised at high latitudes in the Northern hemisphere, coincided with Scandinavia's southern paleopoles for 600-530 my. Component B is almost antiparallel to component A. It corresponds to some short events of normal polarity in the Early and Late Vendian. Component C, whose paleopoles are located at near-equatorial lattitudes, is probably associated with later remagnetisation of the original NRM. The carriers of magnetisation components A and B in basalts are homogeneous accessory titanomagnetites (TM), whose Curie points (TC) lie in the 260-320 °C range. The magnetic phases with TC > 550 °C appearing in some basalts of North Volyn have been caused by high-temperature oxidation during a more recent volcanic activity period of the central type. The hypothesis of a genetic link existing between such oxidation, high-temperature remagnetisation of basalts and the high concentration of native copper in them, is substantiated. Some tectonic aspects of the problem are discussed.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский